1999
DOI: 10.1577/1548-8659(1999)128<0144:daspos>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diel and Seasonal Patterns of Spotted Gar Movement and Habitat Use in the Lower Atchafalaya River Basin, Louisiana

Abstract: We used radiotelemetry to determine diel and seasonal movements, habitat use, and home range behavior of 37 adult spotted gars Lepisosteus oculatus in the Atchafalaya River basin, Louisiana. The Atchafalaya River exhibits a distinct spring flood pulse each year, inundating a 3,640-km 2 floodplain that includes a complex network of canals, bayous, and lakes. During nonflood months, diel locations of 27 fish recorded at 2-h intervals (median ϭ 24 locations/fish) indicated that most spotted gars were shoreline or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 24 publications
6
71
1
1
Order By: Relevance
“…7) that was not readily expected given the observed high abundance of gar in SAV beds during the summer collections. But among the upper-estuary species that have strong freshwater affinities, gar are often found in higher-salinity habitats and may move downestuary to overwinter in deeper depressions (Lambou 1952;Snedden et al 1999;Love 2004). Gar are long-lived species (Love 2004) and consume marine species such as blue crabs (Lambou 1952), so that partial retention of the marine d 34 S signal from winter diets could explain the high d 34 S values observed for upper-estuary gar collected in summer.…”
Section: Discussionmentioning
confidence: 99%
“…7) that was not readily expected given the observed high abundance of gar in SAV beds during the summer collections. But among the upper-estuary species that have strong freshwater affinities, gar are often found in higher-salinity habitats and may move downestuary to overwinter in deeper depressions (Lambou 1952;Snedden et al 1999;Love 2004). Gar are long-lived species (Love 2004) and consume marine species such as blue crabs (Lambou 1952), so that partial retention of the marine d 34 S signal from winter diets could explain the high d 34 S values observed for upper-estuary gar collected in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Florida gar in the Everglades have a narrow diet breadth (Loftus, 2000) feeding on other fish, amphibians, grass shrimp, and crayfish. Gar can move long distances (Snedden et al, 1999) and tracking studies in the Everglades have shown Florida gar to travel 5 km or more in one day when water levels drop locally in the dry season (Wolski & Trexler, unpublished data). However, in the wet season when our isotopic data were gathered, most radiotagged gar moved relatively little, displaying nighttime foraging movements from depressions and ponds and returning to the same area each day.…”
Section: Discussionmentioning
confidence: 99%
“…Spawning takes place in waters ranging from 20 to 30°C (Echelle and Riggs 1972), and movement of adults into floodplains and inundated riparian areas is initiated at approx. 15°C in Louisiana (Snedden et al 1999). Similarly, in Rondeau Bay, Lake Erie movement to spawning areas (vegetated wetlands and inundated riparian zones, 0-1 m deep) occurs at approx.…”
Section: Source Populationmentioning
confidence: 97%